Commercial mediation as an institution of the commercial law - Лопушанська, Ольга Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In the article the author of the specific features of commercial mediation as a distinct institution of commercial law, defined its characteristics, principles, composition and duties of the subjects of relations. Based on the study found that commercial mediation is a new economic and legal category for Ukraine that requires proper legal regulation and institutional development.